Effect of Salmonella enterica subspecies enterica serovar Typhimurium and Serratia fonticola on germination of seeds of common crops - Bhoj Raj Singh, Ashvani Kumar, Sugandh Agrawal and Anita Verma (The Journal of Infection in Developing Countries, 2007)
Background: Salmonella enterica subspecies enterica serovar Typhimurium (S. e. e. Typhimurium) and Serratia fonticola were tested to determine their effects on the germination of seeds of 49 and 36 cultivars of crops, respectively.Methodology: Seeds were soaked in water containing 4.20 × 106 CFU per ml of S. e. e. Typhimurium or 4.12 × 106 CFU per ml of S. fonticola for 6 h to expose them to the pathogens before germination.Results: Salmonella e. e. Typhimurium reduced seed germination of 22 cultivars belonging to 15 plant species and 14 genera. S. e. e. Typhimurium increased germination of only one cultivar of muskmelon. Serratia fonticola inhibited seed germination of 19 cultivars belonging to 11 plant species and 10 genera.Conclusions: The study indicated that contamination of seeds by S. e. e. Typhimurium and S. fonticola significantly alters seed germination of a few cultivars of some crops. The effect (inhibition of seed germination) appeared cultivar dependent. Investigation has also indicated that it may be possible to select pathogen-resistant varieties of different crops to increase the harvest and enhance the microbial quality of the crop produced.